Satisfaction With Governmental Risk Communication Both Increases and Decreases COVID-19 Mitigation Behaviours - Darrick Evensen; George Warren; Frederic Bouder (Frontiers Media S.A., 2023)
Objectives: Over 3 years of the COVID-19 pandemic, and intense societal and governmental response, a wealth of research has examined risk perceptions and public risk mitigation behaviours. The vast majority of this inquiry has focused on health risks. Nevertheless, as a "total social fact" influencing nearly every aspect of quotidian life, the pandemic engenders a wide range of risk perceptions.Methods:Via a survey (N = 4,206) of representative samples of the general public in five European countries (Germany, Norway, Sweden, Switzerland, United Kingdom), we explore perceptions of a range of personal/public health, economic, and societal risks. We also investigate the effects of perceptions of official governmental risk communication in one's country on risk perceptions and risk mitigation behaviours.Results: Structural equation modelling reveals that whilst perceptions of effective risk communication directly increase behaviours that mitigate COVID-19 health risks, these same perceptions indirectly decrease behaviour frequency via a mediated relationship with societal risk perceptions.Conclusion: The findings highlight the import of governmental authorities analysing and communicating about the range of risk perceptions citizens might have about a "total social fact" such as COVID-19.